Effect Corporate Social Responsibility on Financial Performance - Kamatra, Novrianty; Kartikaningdyah, Ely (International Journal of Economics and Financial Issues, 2015)
The company must be able to maintain a balance relationships with parties outside the company to do a corporate social responsibility (CSR). CSR is a concept or action taken by the company as a sense of social responsibility to the company and the environment in which they operate, as do an activity that can improve the welfare of local communities and protecting the environment, providing scholarships to children in the area are not able to fund for the maintenance of public facilities, donations to build a village/community facilities that are social and useful for many people, especially people who are in the vicinity of the company is located. CSR is a phenomenon and strategies that companies use to accommodate the needs and interests of its stakeholders. Implementation of CSR by companies can be realized with CSR disclosure disseminated to the public in the annual report (annual report) and the company can be measured through financial performance. This study was conducted to examine the effect of CSR on financial performance as measured by profitability ratios consisting of return on assets (ROA), return on equity (ROE), net profit margin (NPM) and earning per share (EPS). The population used in this study was the company mining and basic industry chemicals listed in Indonesia stock exchange during the period 2009-2012, while the sample used in this study using purposive sampling technique. Samples taken as many as 24 companies. This study used a quantitative approach and the method of multiple linear regression analysis of the data, with the first through the classical assumption. The results of this study indicate that simultaneous CSR and control variables consisting of leverage (DER) and size effect on ROA, ROE, NPM and EPS. CSR only partially significant effect on ROA and NPM and no significant effect on ROE and EPS. Keyword: Corporate Social Responsibility; Return on Assets; Return on Equity; Net Profit Margin; Earning Per Share JEL Classifications: M00